The Impact of Digital Transformation on Risk-Taking: An Empirical Study of Japanese Companies - Shah Mehmood Wagan; Sidra Sidra (Review of Business and Economics Studies, 2024)
Goal: This paper examines the effect of digital transformation on corporate risk-taking in Japanese firms and, more importantly, identifies links between digital technology integration and risk appetite. This study inspects how digital transformation impacts internal control quality, investment efficiency, and general financial soundness, with special emphasis on the differences between state-owned versus non-state-owned enterprises. Methods: The empirical analysis uses the data of Nikkei Index firms from 2010 through 2023. Out of the total, excluding the financial and insurance sectors as well as aberrant statuses in trading, 225 firms resulted in 14,567 observations. The regression models controlled for a number of different factors, such as enterprise size, profitability, and industry type of firm. Results: The empirical evidence based on the pooled sample implies that enhanced digital transformation significantly boosts the capability of corporate risk-taking. Specifically, a comparison of the estimated coefficients obtained across the state-owned enterprises versus their non-state-owned counterparts shows a large difference in the magnitude for the latter. The increasing adoption of digital technologies heightens the propensity of those firms to invest in high-risk investments, hence improving their value at large. Conclusions: The study contributes to an understanding of how digital transformation affects corporate behavior in terms of risk-taking. It underlines the need to develop digital initiatives that contribute to investment efficiency and financial stability. The findings imply that policymakers and business leaders should encourage strategies of digital transformation, especially for non-state-owned enterprises, to achieve economic growth through increased risk-taking ability.